INTERAKSI SOSIAL PECANDU GAME ONLINE MAHASISWI UNRI KELURAHAN TUAH KARYA KECAMATAN TAMPAN KOTA PEKANBARU - Ono Shoky Eandra; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted at Jl HR Soebrantas, Tuah Karya Subdistrict, Tampan Subdistrict by qualitative methods on six research subjects. Data was collected by in-depth interviews. The purpose of the study was to determine the profile and social interaction of online game addicts with the environment. The results showed that the profiles of online game addicts were female students who were in the Faculty of Social Sciences and Social Sciences, namely 4 female students with a major in PGSD, 1 female majored in AP and 1 female majored in IP. The interaction of online game addicts with a good family environment, because for family informants is everything. For the interaction of informants with boarding mates is also good, the informants always cook, eat, exercise, gather and play online games together. Interaction of informants with campus friends is not good, because some of the informants have few friends and do not interact with many students on campus.Keywords: Profile, Social Interaction